2023
DOI: 10.3390/sym15040875
|View full text |Cite
|
Sign up to set email alerts
|

On a Class of Analytic Functions Related to Robertson’s Formula Involving Crescent Shaped Domain and Lemniscate of Bernoulli

Abstract: In this paper, we introduce and study the class of analytic functions in the unit disc, which are derived from Robertson’s analytic formula for starlike functions with respect to a boundary point combined with a subordination involving lemniscate of Bernoulli and crescent shaped domains. Using their symmetry property, the basic geometrical and analytical properties of the introduced classes were proved. Early coefficients and the Fekete–Szegö functional were estimated. Results for both classes were also obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…where E = {exp (z) : z ∈ D}. It can easily be observed that the domains L and E are symmetric with respect to the real axis [8]. Geometric function theory shares a close connection with symmetry.…”
Section: Introductionmentioning
confidence: 97%
“…where E = {exp (z) : z ∈ D}. It can easily be observed that the domains L and E are symmetric with respect to the real axis [8]. Geometric function theory shares a close connection with symmetry.…”
Section: Introductionmentioning
confidence: 97%